Analisis Perilaku Konsumsi Generasi Z terhadap Keputusan Menggunakan QRIS - Farhan Taufiqurrahman; Ladi Wajuba Perdini Fisabilillah (Institut Teknologi dan Bisnis (ITB) Semarang, 2026)
The study aims to analyze the influence of consumption behavior, projected through cultural, social, personal, and psychological factors, through Generation Z's decision to use the Quick Response Code Indonesian Standard (QRIS). The focus subjects were taken from undergraduate students of Economics at Surabaya State University from 2021 to 2024 who are active users of QRIS. Using an associative quantitative approach using primary data to be collected using an online questionnaire distribution. The data analysis technique applied Structural Equation Modeling–Partial Least Square (SEM-PLS) using SmartPLS 4 software. The results of the study showed that four factors of consumption behavior, namely cultural factors, social factors, personal factors, and psychological factors, have a positive and significant impact on students' decisions to use QRIS. Evaluation of the F-square value F2 shows that psychological factors (internal motivation, perceived ease, security, and trust) are the most dominant predictors with the largest effect value of 0.434 in influencing the decision to adopt this digital payment system technology. These findings indicate that a combination of students' internal motivation, the digital culture inherent in the campus environment, and the demands of practicality in Generation Z's lifestyle strengthen the decision to use QRIS in daily economic activities.